ISLAMIC PERSPECTIVE WAGES IN ECONOMIC DEVELOPMENT - Ulil Abshor, Muhammad; Ramadhani , Moch. Syafi’udin (LPPM Universitas KH. A. Wahab Hasbullah, 2019)
Abstrak: Religion, as a belief system, is part and core of society's value system. Religion is a system of values and norms that regulate how to behave. Economics is the study of how humans use uncommon resources to create goods and services that humans need. The relationship between religious development and improving economic status is very important and influences each other. Wage problems are the way employers and the government see workers only as a tool to make money, efficiency and production. For entrepreneurs, wages are part of production costs, so they must be calculated and optimized to increase productivity and work ethic. However, wages are compensation that is very helpful for workers to meet their needs. This is based on Marshall's theory that setting a minimum wage allows the workforce to be healthier, which in turn will result in increased productivity in the long term. However, workers' wages in Islam are determined based on the merits, usefulness and profits of one's work. Keywords: economic development, religious position, wage determination system